Evaluation and Management of Indeterminate Thyroid Nodules: The Revolution of Risk Stratification Beyond Cytological Diagnosis. (25th December 2017) - Valderrabano, Pablo; McIver, Bryan
In accordance with National Guidelines, we currently follow a linear approach to the diagnosis of thyroid nodules, with management decision based primarily on a cytological diagnosis following fine-needle aspiration biopsy. However, 25% of these biopsies render an indeterminate cytology, leaving uncertainty regarding appropriate management. Individualizing the risk of malignancy of these nodules could improve their management significantly. We summarize the current evidence on the relevance of clinical information, radiological features, cytological features, and molecular markers tests results and describe how these can be integrated to personalize the management of thyroid nodules with indeterminate cytology. Several factors can be used to stratify the risk of malignancy in thyroid nodules with indeterminate cytology. Male gender, large tumors (>4 cm), suspicious sonographic patterns, and the presence of nuclear atypia on the cytology are all associated with an increased cancer prevalence. The added value of current molecular markers in the risk stratification process needs further study because their performance seems compromised in some clinical settings and remains to be validated in others. Risk stratification is possible in thyroid nodules with indeterminate cytology using data that are often underused by current guidelines. Future guidelines should integrate these factors and personalize the recommended diagnostic and therapeutic approaches accordingly.